Bruton tyrosine kinase degradation as a therapeutic strategy for cancer - Dobrovolsky, Dennis; Wang, Eric S; Morrow, Sara; Leahy, Catharine; Faust, Tyler; Nowak, Radosław P; Donovan, Katherine A; Yang, Guang; Li, Zhengnian; Fischer, Eric S; Treon, Steven P; Weinstock, David M; et al. (Blood, 2019)
The covalent Bruton tyrosine kinase (BTK) inhibitor ibrutinib is highly efficacious against multiple B-cell malignancies. However, it is not selective for BTK, and multiple mechanisms of resistance, including the C481S-BTK mutation, can compromise its efficacy. We hypothesized that small-molecule-induced BTK degradation may overcome some of the limitations of traditional enzymatic inhibitors. Here, we demonstrate that BTK degradation results in potent suppression of signaling and proliferation in cancer cells and that BTK degraders efficiently degrade C481S-BTK. Moreover, we discovered DD-03-171, an optimized lead compound that exhibits enhanced antiproliferative effects on mantle cell lymphoma (MCL) cells in vitro by degrading BTK, IKFZ1, and IKFZ3 as well as efficacy against patient-derived xenografts in vivo. Thus, "triple degradation" may be an effective therapeutic approach for treating MCL and overcoming ibrutinib resistance, thereby addressing a major unmet need in the treatment of MCL and other B-cell lymphomas.